EVALUASI KEHILANGAN AIR PADA SISTEM DISTRIBUSI PERUMDA AIR MINUM TIRTA MANGUTAMA WILAYAH PELAYANAN KUTA DENGAN METODE STEPTEST - Beratha, I Made Indra; Eryani, I Gusti Agung Putu; Sinarta, I Nengah (Jurnal Ilmiah Teknik Sipil, 2022)
The percentage of water loss (Non-Revenue Water) in the drinking water supply system of Public Company for Drinking Water Tirta Mangutama is currently still above the national standard. In addition to exceeding the standard, this also causes losses to Public Company for Drinking Water Tirta Mangutama . To increase the level of service and losses due to NRW, it is necessary to evaluate the network so that it can be used as the basis for efforts to reduce the level of water loss in the Kuta and Tuban Village Service Areas. Active loss search is one of the measures in order to control water loss. In June 2020 there was a peak of water loss with water loss reaching 1,588,931 m3/month or (48.96%). To reduce the water loss that occurs, tissue evaluation is carried out using the steptest method. And based on the step-test simulation, it was found that there were leaks at several points in the distribution system of Perumda Water Drinking Tirta Mangutama, Kuta Service Area. For this reason, it is necessary to repair pipes and manage pressure so that it can reduce water losses that occur.